THE IMPACT OF INDUSTRY WORK PRACTICES AND WORK MOTIVATION ON WORK READINESS STUDENTS CLASS XII COMPETENCE OF ACCOUNTING IN EAST JAKARTA REGIONAL VOCATIONAL HIGH SCHOOL - Pratiwi, Kartika; Sumiati, Ati; Zulaihati, Sri (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2020)
This study aims to determine the ef ect of Industrial Work Practices and Work Motivation on Work Readiness inClass XII of Accounting Skills Competency in East Jakarta Region State Vocational School. The research method used was a survey method and the data obtained were primary data from a questionnaire with a sample of 122 students. The results of the analysis requirements test show that the data is normally distributed and has a linear relationship. Based on the hypothesis test, it can be concluded that partially and simultaneously industrial work practices and work motivation have a positive and significant effect on job readiness. The magnitude of the influence of the variable industrial work practice and work motivation simultaneously on job readiness is 70.6%.